2020
DOI: 10.1016/j.electstud.2020.102182
|View full text |Cite
|
Sign up to set email alerts
|

When long-distance relationships don't work out: Representational distance and satisfaction with democracy in Europe

Abstract: We assess the impact of party representation on satisfaction with democracy. Our proposition is that such representation is not only about having a chosen party in government; citizens also derive satisfaction from having their views represented by a political party. We test this through an individual-level measure of policy (in) congruence: the ideological distance between a voter and his or her closest party. Via multi-level modelling of European Election Study data from 1989 to 2009, we find that perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Previous studies on the relationship between democratic satisfaction and congruence have noted that including specific policy issues is highly relevant (e.g. Hall & Evans, 2019;van Egmond, Johns & Brandenburg, 2020). For instance, measuring congruence on five issue dimensions, Stecker and Tausendpfund (2016) found that citizens who are more distant from their government are more dissatisfied with democracy.…”
Section: Conceptualising Policy Opinion Congruencementioning
confidence: 97%
“…Previous studies on the relationship between democratic satisfaction and congruence have noted that including specific policy issues is highly relevant (e.g. Hall & Evans, 2019;van Egmond, Johns & Brandenburg, 2020). For instance, measuring congruence on five issue dimensions, Stecker and Tausendpfund (2016) found that citizens who are more distant from their government are more dissatisfied with democracy.…”
Section: Conceptualising Policy Opinion Congruencementioning
confidence: 97%
“…On the one hand, these studies show that a lower individual ideological distance to the government leads to increased political support also outside of the context of winning and losing an election (Ferland, 2021; Henderson, 2008; Mayne & Hakhverdian, 2017; Noordzij et al, 2021; Stecker & Tausendpfund, 2016). On the other hand, some studies argue that the individual ideological congruence with the government moderates the impact of winning or losing: if the government is closer to your own ideological position, the impact of winning or losing the election is less pronounced (Campbell, 2015; Curini et al, 2012; Curini & Jou, 2016; Gärtner et al, 2020; Hobolt et al, 2021; van Egmond et al, 2020).…”
Section: Representation By the Government And Political Supportmentioning
confidence: 99%
“…However, we can tell that the performance of parties, governments and the electoral process affect how citizens evaluate democracy. Reportedly, policy congruence between the citizens and the political elites has an important role in influencing democratic satisfaction (Ferland, 2020; Kim, 2009; Reher, 2015; van Egmond et al, 2020). Besides congruence in policy and ideology, André and Depauw (2017) demonstrate the effect of congruence in how citizens and legislators view the representation process.…”
Section: The Legislators’ Performance and Satisfaction With Democracymentioning
confidence: 99%